What Does 'Natural Capital' Do? The Role of Metaphor in Economic Understanding of the Environment. (1st November 2003) - Akerman, Maria
At the time of its introduction in the end of the 1980s, the concept of natural capital represented new, more ecologically aware thinking in economics. As a symbol of novel thinking, the metaphor of natural capital stimulated a debate between different disciplinary traditions on the definitions of the concept and research priorities and methods. The concept became a means to control the discourse of sustainable development. In this paper, I focus on the power/knowledge implications of the use of the concept, and I follow the career of the concept of natural capital in ecological economic publications between the years 1988 and 2000. The main interests are(1) in the use of the concept to affect the rules according to which claims concerning sustainable development can be made and (2) in the constitution of objects of environmental knowledge.